Improved Campephiline detection: An experiment conducted with the Magellanic Woodpecker - Wynia, Amy L.; Rolland, Virginie; Jimenez, Jaime E. (My University, 2019)
Woodpeckers can be difficult to detect, as they are often cryptic, secretive, occurring in low densities, and wary of humans. Several methods exist to detect woodpeckers (e.g., playback surveys, passive point counts), yet no research has established which technique best detects these elusive picids. Thus, we designed an experiment to determine which of three methods best results in a detection of Magellanic Woodpeckers (Campephilus magellanicus), and if weather variables influence detection probability. Mostly during austral summers 2015-2017, we (a) used a drumming device to simulate a double-knock (i.e., territorial acoustical signal), (b) broadcasted a territorial call, and (c) passively listened (control) for Magellanic Woodpeckers. We conducted our experiment on Navarino Island, Chile, where the Magellanic Woodpecker is the sole picid. The drumming device most effectively influenced the likelihood of a woodpecker detection. The odds of a woodpecker responding to a double-knock were 2.14 times more likely than responding to either a call or control. Moreover, the odds of a woodpecker detection decreased by 42% as wind increased by one category and decreased by 40% for every additional month (i.e., October-March), which was expected because woodpeckers become less territorial as the breeding season progresses. As Campephilus woodpeckers communicate via drums or double-knocks, using a drumming device likely will be an effective technique to detect not only Magellanic Woodpeckers, but other woodpeckers within the Campephilus genus in Central and South America.
Keywords: campephilus; detection technique; drumming device; southern chile